2021
DOI: 10.1111/jerd.12807
|View full text |Cite
|
Sign up to set email alerts
|

Can identical dental shade guides be used interchangeably?

Abstract: Objective: To determine if identical dental shade guides can be used interchangeably considering their precision.Materials and methods: Twenty Vita classical (VC) and Vita 3D-Master (VM) shade guides were subjected to spectrophotometric measurements and their CIELab values were measured in three shade tab regions: incisal, middle, and cervical and also in total. The mean L*, a*, and b* values for analogous shade tabs were calculated to identify CIELab values for typical shades. ΔE 00 color differences between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This study has certain limitations, such as only one type of shade guide used in this study, i.e., VITAPAN 3D Master™, which has too many shades to choose from, causing some confusion, especially for the patients [13,14]. However, if appropriately utilized, the VITAPAN 3D Master™ is made to reduce options to seven in one step, so it shouldn't be a problem.…”
Section: Discussionmentioning
confidence: 99%
“…This study has certain limitations, such as only one type of shade guide used in this study, i.e., VITAPAN 3D Master™, which has too many shades to choose from, causing some confusion, especially for the patients [13,14]. However, if appropriately utilized, the VITAPAN 3D Master™ is made to reduce options to seven in one step, so it shouldn't be a problem.…”
Section: Discussionmentioning
confidence: 99%
“…This is not the case for dental colour: there are no distinct dental shades with the same name, and a shared, universal language exists. A recent study on dental shade guides showed that the Vita Classical and Vita 3D Master guides [44] could be used interchangeably, with a high level of precision for different batches, and satisfactory scores for accuracy; however, the colour differences between distinct basic gingival colours produced by the same manufacturer do exceed the clinical acceptability threshold, which is a desirable characteristic for subjective gingival shade selection (Table 3). Ideally, these colour differences between each of the manufacturer's consecutive basic colours should be homogeneous and equidistantly spaced in the three-dimensional colour space, which is not the case.…”
Section: Null Hypothesesmentioning
confidence: 99%
“…The advantages of this spectrophotometer include its large aperture, enabling it to capture the entirety of the object being measured, as well as its nearperfect scores for repeatability and reproducibility [51], and the fact that it is unaffected by metamerism [69]. Despite these advantages, the 'edge loss phenomenon' does occur, and this could have been minimized by using spectroradiometry [44]. Additional weaknesses include the fact that only one sample was produced for each gingival colour examined and that neither the thickness nor translucency parameters of the gingival shade tabs were taken into consideration.…”
Section: Strengths and Limitations Of The Researchmentioning
confidence: 99%
See 2 more Smart Citations